A large Phyllodes tumor following fennel consumption: Report of a rare case - Navid Kalani; Elham Rafei; Marzieh Haghbeen (Mashhad University of Medical Sciences, 2021)
Introduction: Phyllodes (PTs) tumors are fibroblastic neoplasms of the breast. PTs are relatively rare and include less than 1% of all breast neoplasms. In this study, a case of large tumor of Phyllodes following fennel consumption was reported. Case presentation: The patient was a 47-year-old MCzabz female who complained of a large mass in the left breast and referred to Peymaniyeh Hospital in Jahrom. The patient had a history of infertility for 8 years. She had a 3 cm mass in the left breast from the past 2 years. During previous 7 months, she has used fennel for 3 months due to menstrual irregularities. Conclusion: It seems that the increasing of the breast tumor size in this patient is due to arbitrary consumption of fennel; because fennel has a lot of estrogen, which affects Endoplasmic Reticulum, and tumor filament cells also have beta ER-estrogen receptors; in this patient, the arbitrary consumption of fennel for 3 months has led to the sudden increase in the volume of this mass in the breast.